Tindak Tutur Ilokusi dalam Interaksi Jual Beli di Pasar Bunder dan Implikasinya - Mukti Widayati; Sukarno Sukarno; Wahyu Putri Utami (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
The purpose of this study is to describe the form of illocutionary speech acts in buying and selling interactions in the Bunder Market Sragen and their implications for learning Indonesian in high school. This study used descriptive qualitative method. The method used to collect data in this research is the listening method, free listening and speaking, and note-taking techniques. The method used in analyzing the data is the matching method with an advanced technique, namely the determining element sorting technique (PUP). The data in this study is the form of illocutionary speech acts delivered by sellers and buyers of clothing at the Bunder Market Sragen. The results of this study found the forms of illocutionary speech acts, namely: assertive speech acts (stating, complaining, refusing), directive speech acts (offering, asking), expressive speech acts (insinuating, thanking, praising), commissive speech acts (promising, offering, swear) and its implications for learning negotiating texts for class X in high school. Keywords: implication, round market, illocutionary speech act.